2017
DOI: 10.1093/ptj/pzx101
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Based Interventions for Neck Pain in Office Workers: Systematic Review and Meta-Analysis

Abstract: Workplace-based strengthening exercises were effective in reducing neck pain in office workers who were symptomatic, and the effect size was larger when the exercises were targeted to the neck/shoulder. Future RCTs of ergonomic interventions targeted at office workers who are symptomatic are required. More research on neck pain prevention is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 59 publications
6
102
0
3
Order By: Relevance
“…In addition, recent review evidence suggests that workplace interventions may improve mental health [177,178], the ability to perform occupational tasks fully [179], and adverse musculoskeletal symptoms (e.g. neck and shoulder pain) [176,[180][181][182], though higher quality studies are still needed to identify the most promising interventions. Evidence has also shown that increasing PA levels may be advantageous to employers through reduced absenteeism [183,184] and increased productivity [185].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent review evidence suggests that workplace interventions may improve mental health [177,178], the ability to perform occupational tasks fully [179], and adverse musculoskeletal symptoms (e.g. neck and shoulder pain) [176,[180][181][182], though higher quality studies are still needed to identify the most promising interventions. Evidence has also shown that increasing PA levels may be advantageous to employers through reduced absenteeism [183,184] and increased productivity [185].…”
Section: Discussionmentioning
confidence: 99%
“…Only for the mUTR would the 20RM evoke intensities >60% MVE that is normally considered to be most efficient for a training effect. From a pain reduction perspective, the high intensive exercises have been shown to be most effective and, therefore, the 12RM might be the best gain for the work time invested into exercises at the workplace [11,18].…”
Section: Contraction Intensitiesmentioning
confidence: 99%
“…To access the activation level, electromyography (EMG) is commonly used to measure the activity of the specific muscles that are involved in an exercise [16,17]; the bilateral upper trapezius muscle (mUTR), upper neck extensor muscles (mUNE), and sternocleidomastoideus muscle (mSCM) were the muscle groups included here. In the prevention and treatment of neck and shoulder pain such EMG measurements can ensure that a given mode and intensity of training will activate the target muscles to the sufficient level [18]. In addition, EMG measures allow for exploratory analysis, such as the development of muscle fatigue during multiple repetitions that might be an indicator of the long-term effect on hypertrophy, as well as the reduced perception of pain.…”
Section: Introductionmentioning
confidence: 99%
“…The built environment directly impacts human health and well-being, making building design and operation crucial for managing and improving public health [2][3][4]. Human outcomes frequently identified as being impacted by the built environment include comfort (e.g., thermal [5] and acoustic comfort [6,7]), performance [8,9], sleep [10], stress [11,12], pollutant exposure [13], and a wide range of other health and behavioral outcomes, such as musculoskeletal pain [14], posture [15], pathogen transmission [16][17][18], allergen exposure [19,20], workplace collaboration [21], and privacy [22,23].…”
Section: Introductionmentioning
confidence: 99%